Pengembangan e-komik matematika berbasis etnomatematika betawi untuk meningkatkan literasi matematika siswa SMK - Nuraita, Nurjana; Suhendri, Huri; Mulyatna, Fauzi (International Journal of Progressive Mathematics Education, 2025)
Purpose: This study aims to develop a mathematics e-comic based on Betawi ethnomathematics as an alternative instructional medium for tenth-grade vocational high school (SMK) students, thereby providing learning materials that are both contextual and engaging. Design/methodology/approach: Employing the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), this research involved a limited trial across three vocational high schools. Data collection instruments encompassed needs analysis questionnaires, validation sheets from experts (subject matter, educational technology, and information technology), mathematics literacy tests, and response questionnaires from both teachers and students.Findings: The findings reveal that the e-comic medium falls into the "highly viable" category, based on assessments by subject matter experts (98%), educational technology experts (88.3%), and information technology experts (95.2%). Field trials recorded teacher and student responses at 92.97% and 93% respectively, indicating that the medium is highly practical. Furthermore, the integration of Betawi cultural visual narratives proved effective in contextualizing mathematical concepts.Practical implications: This research presents an innovative instructional medium suitable for deployment in vocational high schools to reinforce conceptual understanding through a cultural approach, while simultaneously holding the potential to enhance students' mathematical literacy within the vocational education setting.Originality/value: The novelty of this study lies in the synthesis of e-comic technology with Betawi ethnomathematics, effectively bridging the gap between the preservation of local heritage and modern, visually interactive mathematics education.   Purpose: Penelitian ini bertujuan mengembangkan e-komik matematika berbasis etnomatematika budaya Betawi sebagai media pembelajaran alternatif untuk siswa kelas X SMK, guna menyediakan materi yang kontekstual dan menarik. Design/methodology/approach: Menggunakan model pengembangan ADDIE (Analysis, Design, Development, Implementation, Evaluation), penelitian ini melibatkan uji coba terbatas pada tiga SMK. Instrumen pengumpulan data meliputi angket analisis kebutuhan, lembar validasi ahli (materi, teknologi pendidikan, dan teknologi informasi), tes literasi matematika, serta angket respons guru dan siswa. Findings: Temuan menunjukkan bahwa media e-komik berada pada kategori sangat layak berdasarkan penilaian ahli materi (98%), ahli teknologi pendidikan (88,3%), dan ahli teknologi informasi (95,2%). Hasil uji coba lapangan mencatat respons guru sebesar 92,97% dan siswa 93%, yang mengindikasikan bahwa media ini sangat praktis. Selain itu, integrasi narasi visual budaya Betawi terbukti efektif dalam mengontekstualisasikan konsep matematika. Practical implications: Hasil penelitian ini menawarkan media pembelajaran inovatif yang layak digunakan di SMK untuk memperkuat pemahaman konsep melalui pendekatan budaya, sekaligus berpotensi meningkatkan literasi matematika siswa dalam lingkungan pendidikan vokasi. Originality/value: Nilai kebaruan studi ini terletak pada penggabungan teknologi e-komik dengan etnomatematika Betawi, menciptakan jembatan antara pelestarian budaya lokal dan pembelajaran matematika modern yang visual dan interaktif.